2022
DOI: 10.7200/esicm.53.280
|View full text |Cite
|
Sign up to set email alerts
|

The effect of social media influencers’ credibility on consumer’s purchase intentions through attitude toward advertisement

Abstract: People incorporate and use the internet in their lives in line with the development of technology. Facebook, Twitter, Instagram, which are especially defined as social media (SM) tools, are among the daily routines of people. Thus, a great transformation has occurred in the SM advertising industry. Social media influencers (SMI) emerged as a result of facilitating communication on SM. Unlike other studies mostly evaluated over celebrities and no detailed on how SMI affects consumers purchasing behavior through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 0 publications
2
15
0
3
Order By: Relevance
“…Here are some names of influencers (celebgrams) who have collaborated, namely endorsements with Avoskin's Instagram account: have not been verified. In their research, Kim dan Jeong in (Ata et al, 2022) argued whether the use of influencers would be more effective in determining consumer attitudes towards advertising, and it was found that influencers were known to be more attractive than celebrities in the world of advertising through their social media.…”
Section: Celebgram Selection Criteriamentioning
confidence: 99%
See 4 more Smart Citations
“…Here are some names of influencers (celebgrams) who have collaborated, namely endorsements with Avoskin's Instagram account: have not been verified. In their research, Kim dan Jeong in (Ata et al, 2022) argued whether the use of influencers would be more effective in determining consumer attitudes towards advertising, and it was found that influencers were known to be more attractive than celebrities in the world of advertising through their social media.…”
Section: Celebgram Selection Criteriamentioning
confidence: 99%
“…In Their Study, (Ata et al, 2022) said that unlike celebrities in general, influencers succeed in influencing consumers as representatives of a brand or product. They also evaluated that the impact and ability of influencers on advertising depends more on their popularity and does not need a fit between the product and their influencer.…”
Section: Celebgram Selection Criteriamentioning
confidence: 99%
See 3 more Smart Citations